Normalized Born Approximation-Based Two-Stage Reconstruction Algorithm for Quantitative Fluorescence Molecular Tomography. (27th September 2012) - Yi, Huangjian; Chen, Duofang; Li, Wei; Zhou, Shuang; Ning, Miao; Zhu, Shouping; Tian, Jie; Liang, Jimin
Abstract : Fluorescence molecular tomography (FMT) is a promising technique for in vivo small animal imaging. In this paper, a two-stage reconstruction method based on normalized Born approximation is developed for FMT, which includes two steps for quantitative reconstruction. First, the localization of fluorescent fluorophore is determined by l 1 -norm regularization method. Then, in the location region of fluorophore, which is provided by the first stage, algebraic reconstruction technique (ART) is utilized for the fluorophore concentration reconstruction. The validity of the two-stage quantitative reconstruction algorithm is testified by simulation experiments on a 3D digital mouse atlas and physical experiments on a phantom. The results suggest that we are able to recover the fluorophore location and concentration.